New Dihydro OO'Bis(Salicylidene) 2,2' Aminobenzothiazolyl Borate Complexes: Kinetic and Voltammetric Studies of Dimethyltin Copper Complex with Guanine, Adenine, and Calf Thymus DNA (Bioinorganic Chemistry and Applications)
The newly synthesized ligand, dihydro OO'bis(salicylidene) 2,2' aminobenzothiazolyl borate (2), was derived from the reaction of Schiff base of 2-aminobenzothiazole and salicylaldehyde with KBH 4 . Cu II (3) and Zn II (4) complexes of (2) were synthesized and further metallated with dimethyltindichloride to yield heterobimetallic complexes (5) and (6). All complexes have been thoroughly characterized by elemental analysis, and IR, NMR, EPR, and UV-Vis spectroscopy and conductance measurements. The spectroscopic data support square planar environment around the Cu II atom, while the Sn IV atom acquires pentacoordinate geometry. The interaction of complex (5) with guanine, adenine, and calf thymus DNA was studied by spectrophotometric, electrochemical, and kinetic methods. The absorption spectra of complex (5) exhibit a remarkable "hyperchromic effect" in the presence of guanine and calf thymus DNA. Indicative of strong binding of the complex to calf thymus DNA preferentially binds through N 7 position of guanine base, while the adenine shows binding to a lesser extent. The kinetic data were obtained from the rate constants, k obs , values under pseudo-first-order conditions. Cyclic voltammetry was employed to study the interaction of complex (5) with guanine, adenine, and calf thymus DNA. The CV of complex (5) in the absence and in the presence of guanine and calf thymus DNA altered drastically, with a positive shift in formal peak potential E pa and E pc values and a significant increase in peak current. The positive shift in formal potentials with increase in peak current favours strong interaction of complex (5) with calf thymus DNA. The net shift in E 1/2 has been used to estimate the ratio of equilibrium constants for the binding of Cu(II) and Cu(I) complexes to calf thymus DNA.